1991
DOI: 10.2337/diacare.14.8.732
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Acarbose as First-Line Drug in NIDDM Insufficiently Treated With Diet Alone

Abstract: Extrapolation shows that acarbose is an efficient and acceptable drug for the treatment of NIDDM with poor metabolic control by diet alone. It has beneficial effects on postprandial hyperinsulinemia and postprandial hypertriglyceridemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
1
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(95 citation statements)
references
References 8 publications
4
88
1
2
Order By: Relevance
“…This may suggest that the groups of patients, with comparable responses to the meal test at baseline, became distinct following acarbose therapy. However, mean postprandial plasma glucose was not changed by this therapy, in agreement with some (13) but not all previous reports (10,11,14). Based on potential hemodynamic benefits (5,15) related to the improvement in metabolic control, as expressed by decreased glycosylated hemoglobin, the effects of acarbose on BP of hypertensive diabetic patients were investigated.…”
Section: Discussionsupporting
confidence: 63%
“…This may suggest that the groups of patients, with comparable responses to the meal test at baseline, became distinct following acarbose therapy. However, mean postprandial plasma glucose was not changed by this therapy, in agreement with some (13) but not all previous reports (10,11,14). Based on potential hemodynamic benefits (5,15) related to the improvement in metabolic control, as expressed by decreased glycosylated hemoglobin, the effects of acarbose on BP of hypertensive diabetic patients were investigated.…”
Section: Discussionsupporting
confidence: 63%
“…All but three studies (33,36,38) showed one or more deficiency or insufficient reporting of the main quality criteria. Pharmaceutical companies sponsored 33 studies, 2 studies were sponsored by another fund, 1 study was not sponsored, and possible sponsoring was unclear for 5 studies.…”
Section: Discussionmentioning
confidence: 99%
“…There should be little effect on lipid metabolism based on this mode of action, though some reports have indicated a slight suppression of postprandial triglyceride levels. 6,7) A recent clinical study showed that a long-acting sulfonylurea, glibenclamide could improve postprandial hypertriglyceridemia in patients with type 2 diabetes. 8) However, sulfonylureas have an inadequate effect on postprandial hyperglycemia.…”
mentioning
confidence: 99%